Molecular Activities and Mechanisms of Action of Substances and Molecules from Medicinal Plants from Sub-Saharan Africa on Prostate and Cervical Cancer Cells - Coulibaly, Liz Laetitia; Bayala, Bagora; Simpore, Jacques (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Background Despite years of medical research, cancer remains a major public health problem worldwide, particularly in Africa. The cost, duration, and toxicity of currently available treatments are all drawbacks. Plant secondary metabolites are significant anticancer compounds. Already used in traditional health systems, plants are currently the subject of numerous studies to discover new anti-cancer drugs. Objective This review assesses the literature on the cytotoxic effect of plant substances (extracts) and molecules on prostate and cervical cancer cell lines. Methods PubMed, Science Direct, and Google Scholar were used to find in vitro studies carried out between 2006 and 2023 related to the cytotoxicity of extracts, substances and/or molecules from plants harvested in sub-Saharan Africa against prostate and/or cervical cancer cell lines. Results A total of 36 reports on the cytotoxic potential of 96 medicinal plants from sub-Saharan Africa were extracted from the selected databases. All the plants listed had a cytotoxic effect on prostate and/or cervical cancer cells. Some plant extracts or molecules showed significant activity with an IC50< 20 µg/ml. Burkina Faso and South Africa had the most plant extracts tested for prostate and cervical cancer, respectively. Conclusion A total of 36 reports on the cytotoxic potential of 96 medicinal plants from sub-Saharan Africa were extracted from the selected databases.
Keywords: Plants